Transparency and Accountability in Village Financial Management to Improve Community Welfare: An Analysis of Village Development Trends in Indonesia - Marcio J. C. Rosa Lay; Karno, Karno (PT. ALHAFI BERKAH INDONESIA, 2025)
This study analyzes the transparency and accountability of village financial management in improving community welfare in Indonesia. The research method uses a qualitative approach with descriptive analysis of secondary data from publications of the Central Statistics Agency and Ministry of Finance for the period 2022-2024. The results show that Village Fund allocation has increased significantly from IDR 72 trillion in 2024 to IDR 71 trillion in 2025, with incentive distribution to 15,124 outstanding villages. The implementation of digital village financial systems has increased financial reporting transparency by 68% throughout Indonesia. The accountability of village financial management shows improvement through the application of measurable technical, administrative, and legal principles. Community participation in village financial supervision reaches 45% of the total village population. These findings indicate that transparency and accountability in village finances are positively correlated with improved welfare of rural communities. Research recommendations include strengthening village information systems, increasing village apparatus capacity, and optimizing community participation in village financial management.